Autologous peripheral blood stem cell transplantation and the role of lenalidomide in patients affected by poems syndrome. Issue 2 (15th September 2017) - Autore, Francesco; Innocenti, Idanna; Luigetti, Marco; Piccirillo, Nicola; Sora, Federica; Chiusolo, Patrizia; Sica, Simona; Bacigalupo, Andrea; Laurenti, Luca
Abstract: POEMS syndrome is a rare paraneoplastic condition, with a poorly understood pathogenesis. High dose chemotherapy followed by autologous stem cell transplantation (ASCT) has been reported to be an effective therapeutic option for patients with good performance status. Here, we review the role of ASCT for POEMS syndrome and discuss indications together with advantages and disadvantages, and related issues such lenalidomide given before or after ASCT, VEGF levels as a marker of disease, and different regimens for stem cell mobilization.